2019
DOI: 10.1038/s41598-019-48060-0
|View full text |Cite|
|
Sign up to set email alerts
|

Interspecific competition among catch crops modifies vertical root biomass distribution and nitrate scavenging in soils

Abstract: The potential of a plant species to acquire nutrients depends on its ability to explore the soil by its root system. Co-cultivation of different species is anticipated to lead to vertical root niche differentiation and thus to higher soil nutrient depletion. Using a qPCR-based method we quantified root biomass distribution of four catch crop species in vertical soil profiles in pure vs. mixed stands. Pure stands of mustard and phacelia robustly reached 70 cm soil depth, while oat preferably colonized upper soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…It has been shown that plant-plant competition decreases the total biomass production both for interspecific (Heuermann et al 2019) and intraspecific competition (Zhou et al 2018). We also showed that shoot biomass decreased in the presence of competition.…”
Section: Intraspecific Competition Reduces Shoot But Not Root Biomass Productionsupporting
confidence: 69%
“…It has been shown that plant-plant competition decreases the total biomass production both for interspecific (Heuermann et al 2019) and intraspecific competition (Zhou et al 2018). We also showed that shoot biomass decreased in the presence of competition.…”
Section: Intraspecific Competition Reduces Shoot But Not Root Biomass Productionsupporting
confidence: 69%
“…There is less debate with regard to the effect of competition (whether inter- or intraspecific) on biomass production, with several studies showing a decrease in plant biomass when growing in competition (Zhou et al 2017; Heuermann et al 2019). We also show that shoot biomass decreased in the presence of competition.…”
Section: Discussionmentioning
confidence: 99%
“…Such highly dynamic architectural responses of roots allow plants to optimize spatially defined soil exploration, improving plant performance under challenging N conditions. For instance, plant species forming more root biomass in deeper soil layers also deplete nitrate pools more efficiently ( Heuermann et al , 2019 ), and local proliferation of lateral roots into N-rich soil patches contributes significantly to plant N nutrition ( Hodge et al , 1999 ; Robinson et al , 1999 ; Ma et al , 2013 ). Under N-deficient conditions, plants develop a steeper root angle, which promotes deep rooting and facilitates N acquisition from subsoil layers, especially under soil conditions with high potential for nitrate leaching ( Trachsel et al , 2013 ; Saengwilai et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%